Protease inhibitors: recent advancement in its usage as a potential biocontrol agent for insect pest management - Singh, Sujata; Singh, Archana; Kumar, Sumit; Mittal, Pooja; Singh, Indrakant K. (Insect science, 2020)
Plant‐derived protease inhibitors (PIs) are a promising defensin for crop improvement and insect pest management. Although agronomist made significant efforts in utilizing PIs for managing insect pests, the potentials of PIs are still obscured. Insect ability to compensate nutrient starvation induced by dietary PI feeding using different strategies, that is, overexpression of PI‐sensitive protease, expression of PI‐insensitive proteases, degradation of PI, has made this innumerable collection of PIs worthless. A practical challenge for agronomist is to identify potent PI candidates, to limit insect compensatory responses and to elucidate insect compensatory and resistance mechanisms activated upon herbivory. This knowledge could be further efficiently utilized to identify potential targets for RNAi‐mediated pest control. These vital genes of insects could be functionally annotated using the advanced gene‐editing technique, CRISPR/Cas9. Contemporary research is exploiting different in silico and modern molecular biology techniques to utilize PIs in controlling insect pests efficiently. This review is structured to update recent advancements in this field, along with its chronological background.